Interação entre universidade e empresa : a formação interdisciplinar ampla - Cardoso, Aline de Oliveira da Conceição (2016)
This volume presents the thesis developed in the Humanities School, in the Education Post-graduate Program of Pontifícia Universidade Católica do Rio Grande do Sul – PUCRS, in the Politics Formation and Education Practices’ research line. We investigated the contributions and limitations to the wide interdisciplinary formation, here known as the one which contemplates the formal and tacit knowledge, propitiated by the articulation between company and university, via projects in PUCRS’ Technological Park, TECNOPUC, to the formation of Computer Science Post-graduate student, in Computer College/PUCRS. We addressed the contemporary context of knowledge production, the interdisciplinary concept, the origin and concepts of technological parks presented by area’s entities and associations, as well as we brought a little bit of the historical context, mission and structure of TECNOPUC. The research’s problem contemplates the approach between university and company favors the societies’ problems resolution, via technological parks, where opportunities emerge and, as well, conflicts of interest due to expectations related to projects’ results, by the company, and the university’s forming mission. The adopted question of the research was: What are the contributions, tensions and implications to the wide interdisciplinary formation of the Computer Science Post-graduate student, that come from the partnership between the Computer Science Post-graduate Program/PUCRS and TECNOPUC companies? From the survey of the knowledge state, we built a theoretic referential with authors such as: Boaventura de Sousa Santos, Hilton Japiassu, Ivani Fazenda, Arlindo Philippi Jr, Levy, Zouain and Plonski, Henry Etzkowitz, Marília Morosini, and others, besides all legislation contribution. About the research’s methodological organization, we chose the qualitative nature phenomenological approach, in exploratory level, in an ethnographic case study; for that, bibliographic and documental researches were used. For the data collection, were also used as instruments the semi structured interview application and online survey. As data analysis’ method the Discursive Textual Analysis, by Moraes and Galiazzi, was used.